Preparation method of catalyst for preparing monomethylamine

Through the multi-step modification of mordenite, a catalyst with selectivity of high-monomethylamine was prepared, which solved the energy consumption and cost problems caused by the backdoor of dimethylamine and trimethylamine in the existing processes, and achieved more efficient monomethylamine production.

CN119702054APending Publication Date: 2025-03-28WANHUA CHEM (SICHUAN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510002477.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing monomethylamine production process, the back doping of dimethylamine and trimethylamine leads to an increase in separation energy consumption and a higher production cost. It is necessary to develop a catalyst with high monomethylamine selectivity to improve reaction selectivity and reduce energy consumption.

Method used

Catalysts with high methylamine selectivity were prepared by synthesis of mordenite and subjected to acid site modification, microemulsion preparation, catalyst modification, extraction treatment, metal ion soaking, pH adjustment and binder addition.

Benefits of technology

This catalyst significantly improves the selectivity of methylamine, reduces the backdoor of dimethylamine and trimethylamine, reduces production energy consumption and cost, and improves the stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225768740000091
    Figure BDA0005225768740000091
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing monomethylamine under the condition of high temperature of methanol and liquid ammonia, which has high monomethylamine selectivity and higher stability, and can greatly improve the dimethylamine return proportion in the existing monomethylamine process and reduce the production energy consumption of monomethylamine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a method for preparing a catalyst with high monomethylamine selectivity. Technical Background

[0002] At present, the market for dimethylamine is weak, and monomethylamine, as a raw material for the synthesis of NMP, has good market economic benefits. At present, the mainstream process for producing monomethylamine is to mix methanol and liquid ammonia under catalyst conditions, and then add a large amount of dimethylamine and trimethylamine back into the reaction system to increase the output of monomethylamine by inhibiting the reaction balance. However, a large amount of back mixing will increase the separation energy consumption and the production cost is high.

[0003] In view of this situation, it is necessary to develop a catalyst with high monomethylamine selectivity to increase the selectivity of monomethylamine in the reaction, reduce the back-doping of dimethylamine and trimethylamine, and reduce the production cost of the device. Summary of the invention

[0004] The first object of the present invention is to provide a catalyst for preparing monomethylamine under high temperature conditions of methanol and liquid ammonia, which has high monomethylamine selectivity and high stability, can greatly improve the return ratio of dimethylamine in the current monomethylamine process, and reduce the energy consumption of monomethylamine production.

[0005] The second object of the present invention is to provide a method for preparing the catalyst.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a catalyst with high monomethylamine selectivity mainly comprises the following steps:

[0008] 1) Synthesis of mordenite: mordenite is synthesized by hydrothermal method using silicon oxide, sodium hydroxide, sodium aluminate, water and other raw materials;

[0009] 2) Acid site modification: soak the mordenite in an organic phosphorus and phosphoric acid solution for 1-5 hours, then filter, dry and calcine; repeat this step 2-5 times;

[0010] 3) Preparation of microemulsion: preparing an aqueous solution of an active metal salt, dissolving the aqueous solution in a water-insoluble dispersant in a certain proportion, and preparing a microemulsion containing small droplets by stirring, ultrasound, etc.;

[0011] 4) Catalyst modification: the above-mentioned mordenite is added to the microemulsion, and ultrasonic or stirring is performed to allow the metal salt droplets to enter the interior of the mordenite to modify the interior of the mordenite;

[0012] 5) Extraction treatment: adding an extractant to the mordenite-microemulsion mixture, extracting the mordenite with the extractant, and then filtering and drying the mordenite for later use;

[0013] 6) Metal ion soaking: soak the dried mordenite in an organic alkali metal, then filter, dry and cool; repeat this step 2-5 times and take it out for use;

[0014] 7) pH adjustment: soak the mordenite in an alkali metal salt solution (control the solution pH=10-14), then filter, dry, cool, and take out for use;

[0015] 8) Catalyst molding: Add a certain amount of binder to the above-mentioned mordenite, knead it into a shape, and then dry and calcine it to obtain the catalyst.

[0016] The catalyst used in the present invention is mainly composed of mordenite, which has a large specific surface area. At the same time, the aluminum in the zeolite can provide active sites for the reaction, and is very suitable for use as a catalyst.

[0017] In the present invention, the mordenite synthesized in step 1 needs to have a silicon-aluminum ratio of 10-30, preferably 18-24.

[0018] In the present invention, in step 2, the concentration of the organic phosphorus and phosphoric acid-like solution is 0.1%-10wt%, preferably 0.5-5%, more preferably 3-4.5%;

[0019] The organophosphorus and quasi-phosphoric acid are one or more of phosphoric acid, phosphorous acid, parathion, methyl phosphate, and methylene phosphate, preferably phosphoric acid and methyl phosphate. Preferably, the phosphoric acid concentration in the organophosphorus solution is 0.5-5wt%, preferably 1-2wt%, and the methyl phosphate concentration is 1-5wt%, preferably 2-3wt%;

[0020] The mass ratio of the organic phosphorus and phosphoric acid-like solution to the mordenite is 1:(0.01-1), preferably 1:(0.1-0.5);

[0021] In the step 2, the product is filtered, dried and then placed in a muffle furnace and calcined at 150-350° C. for 1-4 hours.

[0022] In step 3 of the present invention, the active metal salt is one or more of ferric nitrate, zinc phosphate, titanium chloride, sodium titanium phosphate, and ferric phosphate; the concentration of the active metal salt aqueous solution is 0.1-10 mol / L, preferably 0.5-5 mol / L, more preferably 1-3 mol / L;

[0023] Preferably, the active metal salts are ferric phosphate and titanium chloride. In the metal salt aqueous solution, the concentration of ferric phosphate is 0.1-5 mol / L, preferably 1-2 mol / L, and the concentration of titanium chloride is 0.1-5 mol / L, preferably 1-2 mol / L.

[0024] The dispersant is selected from one or more water-insoluble organic solvents such as acetone, methyl acetate, ether, benzene, etc., preferably methyl acetate;

[0025] Preferably, the mass ratio of the active metal salt solution to the dispersant is 0.1-50%, preferably 3-15%;

[0026] The ultrasonic condition is 100-150 Hz, and the ultrasonic treatment time is 0.5-2 h.

[0027] In the step 4, the mass ratio of mordenite to microemulsion is (0.01-0.5):1, preferably (0.05-0.2):1;

[0028] The ultrasonic condition is 50-200 Hz;

[0029] The stirring speed is controlled to be 100-200 rpm, and the stirring time is controlled to be 0.5-2h;

[0030] By stirring, the tiny droplets in the microemulsion can enter the pores of the molecular sieve and interact with the internal structure of the molecular sieve.

[0031] In step 5, the extractant is one or more water-soluble solvents such as ethanol, propanol, methanol, etc., preferably ethanol;

[0032] In step 5, the mass ratio of the extractant to the mordenite-microemulsion mixture is 0.05-10:1, preferably 2-5:1;

[0033] The drying temperature is 120-200° C., and the drying time is 2-3 hours.

[0034] In step 6, the organic alkali metal is one or more of sodium ethoxide, potassium ethoxide, and sodium propoxide;

[0035] Furthermore, the mass ratio of mordenite to organic alkali metal is 0.01-1:1, preferably 0.1-0.5:1; the soaking time is 0.1-3h;

[0036] The drying temperature is 100-150° C., and the drying time is 1-5 hours.

[0037] In step 7, the alkali metal salt is one or more of sodium phosphate, potassium phosphate, sodium phosphite, and potassium phosphite;

[0038] The mass ratio of mordenite to alkali metal salt solution is (0.01-1):1, preferably (0.05-0.2):1, and the soaking time is 1-3h, preferably 1h;

[0039] In step 8, the binder used is one or more of magnesium aluminum spinel and γ-Al2O3, preferably magnesium aluminum spinel. The binder can not only help the catalyst provide active sites, but also improve the strength of the catalyst;

[0040] In step 8, the mixing ratio of mordenite, binder and water is 100:(1-40):(1-40), preferably 100:(2-20):(2-20);

[0041] The calcination atmosphere is an inert gas atmosphere, preferably helium. The calcination is a two-stage sintering, the first stage sintering temperature is 200-400°C, preferably 350°C, the sintering time is 1-3h, preferably 2h; the second stage sintering temperature is 500-800°C, preferably 600°C, the sintering time is 1-3h, preferably 2h.

[0042] The present invention also relates to the application of the catalyst in the preparation of monomethylamine.

[0043] The positive effects of the present invention are:

[0044] 1) By replacing acidic ions, the active sites in the molecular sieve are changed to increase the methylamine synthesis reaction activity of the catalyst;

[0045] 2) By preparing a microemulsion, 3-8 nm metal salt droplets are allowed to enter the catalyst pores to modify the internal structure of the catalyst;

[0046] 3) Treating with an extractant to precipitate active metal salts inside the catalyst pores;

[0047] 4) Through organic alkali metal treatment, the pore structure of the catalyst is changed, and the active metal salt is locked inside the molecular sieve; the metal salt interacts with the active sites of the molecular sieve inside the molecular sieve to improve the selectivity of the catalyst. DETAILED DESCRIPTION

[0048] The present invention will now be further described by way of examples. The examples are only used to specifically illustrate the present invention and are not intended to limit the scope of the present invention.

[0049] In the following specific embodiments of the present invention:

[0050] All chemicals were from Beijing Inokai Technology Co., Ltd. and were of analytical grade;

[0051] The purity of the product was analyzed by liquid chromatography, and the gas chromatograph was Agilent 8890B produced by Agilent.

[0052] Example 1

[0053] (1) controlling the raw materials n (silicon oxide), n (sodium hydroxide), n (sodium aluminate), and n (water) to 20:25:1:350, and synthesizing mordenite with a silicon-aluminum ratio of 20 by a hydrothermal method at 200° C.;

[0054] (2) The catalyst was modified by using phosphoric acid and methyl phosphate: the concentration of phosphoric acid in the organic phosphorus solution was 2wt%, and the concentration of methyl phosphate was 2.5wt%; the mass ratio of the organic phosphorus solution to the mordenite was 1:0.2, and the soaking time was 2h. The mordenite was then filtered, dried, and placed in a muffle furnace for sintering at 220°C for 2h. This was repeated three times and then taken out for use;

[0055] (3) using iron phosphate, sodium titanium phosphate, zinc phosphate, and phosphoric acid as active metal salts to prepare an aqueous solution, wherein the concentration of iron phosphate is 1 mol / L, the concentration of sodium titanium phosphate is 0.5 mol / L, the concentration of zinc phosphate is 1 mol / L, and the concentration of phosphoric acid is 1 mol / L; using methyl acetate as a dispersant, the mass ratio of the active metal salt solution to the dispersant is 0.05:1, and placing the microemulsion in a 120 Hz ultrasound treatment for 0.5 h;

[0056] (4) Add the mordenite prepared in step (2) to the microemulsion, control the mass ratio of mordenite to microemulsion to be 0.1:1, control the stirring speed to be 100 rpm, and stir for 0.5 h.

[0057] (5) Using ethanol as an extractant to extract the mordenite. The mass ratio of the extractant to the mordenite-microemulsion mixture is 1:0.2, and the stirring time is 1 hour; after extraction, filtering, drying at 120°C, and the drying time is 2 hours;

[0058] (6) Soaking the dried mordenite in sodium ethoxide: the mass ratio of mordenite to sodium ethoxide is 0.1:1, and the soaking time is 0.5 h; then filtering and drying, the drying temperature is 120° C., and the drying time is 1 h; repeating this step 3 times;

[0059] (7) soaking the mordenite in a sodium phosphate aqueous solution with a pH of 12, controlling the mass ratio of the mordenite to the sodium phosphate solution to be 0.1:1, soaking for 1 hour, filtering and drying, and then setting aside;

[0060] (8) Take 100 g of mordenite, add 20 g of magnesium aluminum spinel and 20 g of water, mix well and extrude into a column with a diameter of 2 mm and a length of 1 cm, dry, and then calcine in a helium atmosphere. The first sintering temperature is 350°C and the sintering time is 2 h; the second sintering temperature is 600°C and the sintering time is 2 h, to obtain catalyst 1#.

[0061] Example 2

[0062] (1) controlling the raw materials n (silicon oxide), n (sodium hydroxide), n (sodium aluminate), and n (water) to 24:25:1:300, and synthesizing mordenite with a silicon-aluminum ratio of 24 by a hydrothermal method at 200° C.;

[0063] (2) The catalyst was modified by using phosphoric acid and methyl phosphate: the concentration of phosphoric acid in the organophosphorus solution was 2 wt %, and the concentration of methyl phosphate was 2.5 wt %; the mass ratio of the organophosphorus solution to the mordenite was 1:0.3, and the soaking time was 1.5 h; the mordenite was then filtered, dried, and placed in a muffle furnace for sintering at 280° C. for 1.5 h; this was repeated three times and then taken out for use;

[0064] (3) using ferric nitrate, titanium chloride and phosphoric acid as active metal salts to prepare an aqueous solution, wherein the concentration of ferric nitrate is 0.5 mol / L, the concentration of titanium chloride is 1 mol / L, and the concentration of phosphoric acid is 2 mol / L; using acetone as a dispersant, the mass ratio of the active metal salt solution to the dispersant is 0.15:1, and placing the microemulsion in 130 Hz ultrasound for 1 hour;

[0065] (4) Add the mordenite prepared in step (2) to the microemulsion, control the mass ratio of mordenite to microemulsion to be 0.2:1, control the stirring speed to be 100 rpm, and stir for 1.5 h.

[0066] (5) Methanol was used as an extractant to extract the mordenite. The mass ratio of the extractant to the mordenite-microemulsion mixture was 1:0.3, and the stirring time was 0.5 h. After extraction, the mixture was filtered and dried at 120°C for 2 h.

[0067] (6) Soaking the dried mordenite in sodium ethoxide: the mass ratio of mordenite to sodium ethoxide is 0.2:1, and the soaking time is 1 hour; then filtering and drying, the drying temperature is 120°C, and the drying time is 1 hour; repeating this step 3 times;

[0068] (7) Soaking the mordenite in a sodium phosphate solution with a pH of 11, controlling the mass ratio of the mordenite to the sodium phosphate solution to be 0.1:1, soaking for 1.5 hours, filtering and drying, and then setting aside;

[0069] (8) Take 200 g of silk zeolite, add 10 g of γ-Al2O3 magnesium aluminum spinel and 10 g of water, mix well and extrude into a column with a diameter of 1 mm and a length of 1 cm, dry, and then calcine in a helium atmosphere. The first sintering temperature is 200°C and the sintering time is 2 h; the second sintering temperature is 700°C and the sintering time is 2 h, and catalyst 2# is obtained.

[0070] Example 3

[0071] (1) controlling the raw materials n (silicon oxide), n (sodium hydroxide), n (sodium aluminate), and n (water) to 22:25:1:300, and synthesizing mordenite with a silicon-aluminum ratio of 22 by a hydrothermal method at 200° C.;

[0072] (2) The catalyst was modified by phosphorous acid and methyl phosphate: the concentration of phosphorous acid in the organophosphorus solution was 2 wt%, and the concentration of methyl phosphate was 2 wt%; the mass ratio of the organophosphorus solution to the mordenite was 1:0.1, and the soaking time was 1.5 h; the mordenite was then filtered, dried, and placed in a muffle furnace for sintering at 300° C. for 1 h; this was repeated three times and then taken out for use;

[0073] (3) using iron phosphate, titanium chloride and phosphoric acid as active metal salts to prepare an aqueous solution, wherein the concentration of iron phosphate is 0.5 mol / L, the concentration of sodium titanium chloride is 1 mol / L, and the concentration of phosphoric acid is 2 mol / L; using ether as a dispersant, the mass ratio of the active metal salt solution to the dispersant is 0.1:1, and placing the microemulsion in a 150 Hz ultrasound treatment for 0.5 h;

[0074] (4) Add the mordenite prepared in step (2) to the microemulsion, control the mass ratio of mordenite to microemulsion to be 0.15:1, control the stirring speed to be 200 rpm, and stir for 0.5 h.

[0075] (5) Using ethanol as an extractant to extract the mordenite. The mass ratio of the extractant to the mordenite-microemulsion mixture is 1:0.4, and the stirring time is 0.5 h; after extraction, filtering, drying at 120°C, and the drying time is 2 h;

[0076] (6) Soaking the dried mordenite in sodium ethoxide: the mass ratio of mordenite to sodium ethoxide is 0.3:1, and the soaking time is 0.5 h; then filtering and drying, the drying temperature is 120° C., and the drying time is 2 h; repeating this step 3 times;

[0077] (7) soaking the mordenite in a sodium phosphite solution with a pH of 10, controlling the mass ratio of the mordenite to the sodium phosphite solution to be 0.15:1, soaking for 2 hours, filtering and drying, and then setting aside;

[0078] (8) Take 250g of silk zeolite, add 10g of γ-Al2O3 and 15g of water, mix well and extrude into a column with a diameter of 1mm and a length of 1cm, dry, and then calcine in a helium atmosphere. The first sintering temperature is 200℃ and the sintering time is 2h; the second sintering temperature is 600℃ and the sintering time is 2h, and catalyst 3# is obtained.

[0079] Comparative Example 1

[0080] (1) controlling the raw materials n (silicon oxide), n (sodium hydroxide), n (sodium aluminate), and n (water) to 24:25:1:300, and synthesizing mordenite with a silicon-aluminum ratio of 24 by a hydrothermal method at 200° C.;

[0081] (2) The catalyst was modified by using phosphoric acid and methyl phosphate: the concentration of phosphoric acid in the organophosphorus solution was 2 wt %, and the concentration of methyl phosphate was 2.5 wt %; the mass ratio of the organophosphorus solution to the mordenite was 1:0.3, and the soaking time was 1.5 h; the mordenite was then filtered, dried, and placed in a muffle furnace for sintering at 280° C. for 1.5 h; this was repeated three times and then taken out for use;

[0082] (3) using ferric nitrate, titanium chloride and phosphoric acid as active metal salts to prepare an aqueous solution, wherein the concentration of ferric nitrate is 0.5 mol / L, the concentration of titanium chloride is 1 mol / L, and the concentration of phosphoric acid is 2 mol / L; controlling the mass ratio of the catalyst to the metal salt aqueous solution to be 0.2:1, controlling the stirring speed to be 100 rpm, and drying the catalyst after stirring for 0.5 h, the drying temperature is 120°C, and the drying time is 2 h;

[0083] (4) soaking the mordenite in a sodium phosphate solution with a pH of 11, controlling the mass ratio of the mordenite to the sodium phosphate solution to be 0.1:1, soaking for 1.5 hours, filtering and drying, and then setting aside;

[0084] (5) Take 200 g of mordenite, add 10 g of magnesium aluminum spinel and 10 g of water, mix well and extrude into a column with a diameter of 1 mm and a length of 1 cm, dry, and then calcine in a helium atmosphere. The first sintering temperature is 200°C and the sintering time is 2 h; the second sintering temperature is 700°C and the sintering time is 2 h, to obtain catalyst 4#.

[0085] Application Example 1:

[0086] The catalysis was evaluated using a fixed bed pilot plant:

[0087] The fixed bed reactor is a stainless steel tube, 700 mm long, with a stainless steel temperature measuring tube in the center. It uses a single-stage vertical heating furnace, and the reaction temperature is based on the central thermocouple indication. The raw materials pass through the catalyst bed in one direction. Methanol is an analytical reagent and liquid ammonia is industrial grade.

[0088] Catalyst loading: 20 g, reaction temperature: 350 °C, reaction pressure: 3.0 MPa, N / C (molar ratio): 1.9, space velocity: 0.59 h -1 .

[0089] The comparative catalyst is: N-7066 catalyst from BASF.

[0090] The zeolite molecular sieve is: the mordenite with a silicon-aluminum ratio of 20 synthesized in Example 1 without any treatment.

[0091] After the reaction was continued for 1 hour and the system temperature stabilized, data analysis was performed on the products after the reaction. The indicators of the pilot test products are shown in the following table:

[0092] Catalyst Performance Data Sheet

[0093] catalyst Methanol conversion rate Monomethylamine selectivity Dimethylamine selectivity Trimethylamine selectivity Dimethyl ether selectivity 1# 99% 43.1% 18.7% 38.0% 0.01% 2# 99% 37.1% 22.4% 40.2% 0.01% 3# 98% 40.1% 17.7% 41.2% 0.5% 4# 94% 20.1% 26.2% 49.5% 4% Zeolite molecular sieve 85% 15.3% 22.4% 50.1% 11.2% Comparison of catalysts 99% 22.1% 28.5% 48.9% 0.01%

[0094] Application Example 2:

[0095] A fixed bed pilot test equipment was used to conduct a long-term experiment to evaluate the stability of No. 1, No. 4, zeolite molecular sieves and comparative catalysts:

[0096] The fixed bed reactor is a stainless steel tube, 700 mm long, with a stainless steel temperature measuring tube in the center, a single-stage vertical heating furnace, and the reaction temperature is based on the indication of the central thermocouple. The raw materials pass through the catalyst bed once.

[0097] Catalyst loading: 20 g, reaction temperature: 350 °C, reaction pressure: 3.0 MPa, N / C (molar ratio): 1.9, space velocity: 0.59 h -1 . A 120-minute long-term trial was conducted, and the product indicators of the trial are shown in the following table:

[0098] Note: α represents the conversion rate of the single-pass reaction, calculated in terms of methanol; y represents the selectivity of the single-pass reaction for monomethylamine;

[0099] It can be seen from the above table that the structure of the catalyst modified by microemulsion is stable. After a long period of experiment, the catalyst activity has not decreased, and the selectivity of monomethylamine has not declined, which meets the operation requirements of existing industrial equipment.

[0100] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing a catalyst, comprising the following steps: 1) Synthesis of mordenite: Synthesize mordenite with a silicon-aluminum ratio of 10-30, preferably 18-24, by hydrothermal method; 2) Acid site modification: soak the mordenite in an organic phosphorus and phosphoric acid solution, then filter, dry and calcine; Repeat this step 2-5 times; 3) Preparation of microemulsion: preparing an aqueous solution of an active metal salt, and dissolving the aqueous solution in a water-insoluble dispersant to prepare a microemulsion containing small droplets; 4) Catalyst modification: the above-mentioned mordenite is added into the microemulsion, and ultrasonicated or stirred; 5) Extraction treatment: adding an extractant to the mordenite-microemulsion mixture, extracting the mordenite with the extractant, and then filtering and drying the mordenite for later use; 6) Metal ion soaking: soak the dried mordenite in an organic alkali metal, then filter, dry and cool; Repeat this step 2-5 times and take it out for later use; 7) pH adjustment: soak the mordenite in an alkali metal salt solution, filter, dry, cool, and then take out for use; 8) Catalyst molding: Add a binder to the above-mentioned mordenite, knead it into a mold, and then dry and calcine it to obtain the catalyst.

2. The preparation method according to claim 1, characterized in that: In step 2, the concentration of the organic phosphorus and phosphoric acid-like solution is 0.1%-10wt%, preferably 0.5-5wt%; Preferably, the organophosphorus and quasi-phosphoric acid are one or more of phosphoric acid, phosphorous acid, parathion, methyl phosphate, and methylene phosphate, preferably phosphoric acid and methyl phosphate. Preferably, the phosphoric acid concentration in the organophosphorus solution is 0.5-5%wt%, preferably 1-2wt%, and the methyl phosphate concentration is 1-5wt%, preferably 2-3wt%; Preferably, the mass ratio of the organic phosphorus and phosphoric acid-like solution to the mordenite is 1:(0.01-1), preferably 1:(0.1-0.5); Preferably, calcination is performed at 150-350° C. for 1-4 hours.

3. The preparation method according to claim 1, characterized in that: In step 3, the active metal salt is one or more of ferric nitrate, zinc phosphate, titanium chloride, sodium titanium phosphate, and ferric phosphate; the concentration of the active metal salt aqueous solution is 0.1-10 mol / L, preferably 0.5-5 mol / L.

4. The preparation method according to claim 1 or 3, characterized in that: In step 3, the dispersant is selected from one or more of acetone, methyl acetate, ether, and benzene, preferably methyl acetate; Preferably, the mass ratio of the active metal salt solution to the dispersant is 0.1-50%, preferably 3-15%; Preferably, the ultrasonic condition is 100-150 Hz ultrasonic treatment for 0.5-2 h.

5. The preparation method according to claim 1, characterized in that: In step 4, the mass ratio of mordenite to microemulsion is (0.01-0.5):1, preferably (0.05-0.2):1; Preferably, the ultrasonic condition is 50-200 Hz; Preferably, the stirring speed is controlled to be 100-200 rpm, and the stirring time is controlled to be 0.5-2h.

6. The preparation method according to claim 1, characterized in that: In step 5, the extractant is one or more of ethanol, propanol, and methanol, preferably ethanol; Preferably, the mass ratio of the extractant to the mordenite-microemulsion mixture is 0.05-10:1, preferably 2-5:1; Preferably, the drying temperature is 120-200° C., and the drying time is 2-3 hours.

7. The preparation method according to claim 1, characterized in that: In step 6, the organic alkali metal is one or more of sodium ethoxide, potassium ethoxide, and sodium propoxide; Preferably, the mass ratio of mordenite to organic alkali metal is (0.01-1):1, preferably 0.1-0.5:1; Preferably, the soaking time is 0.1-3h; Preferably, the drying temperature is 100-150° C., and the drying time is 1-5 h.

8. The preparation method according to claim 1, characterized in that: In step 7, the alkali metal salt is one or more of sodium phosphate, potassium phosphate, sodium phosphite, and potassium phosphite; Preferably, the mass ratio of mordenite to alkali metal salt solution is (0.01-1):1, and the soaking time is 1-3 hours.

9. The preparation method according to claim 1, characterized in that: In step 8, the binder is one or more of magnesium aluminum spinel and γ-Al2O3; The mixing ratio of mordenite, binder and water is 100:(1-40):(1-40), preferably 100:(2-20):(2-20); Preferably, the calcination atmosphere is an inert gas atmosphere, preferably helium; the calcination is a two-stage sintering, the first stage sintering temperature is 200-400°C, the sintering time is 1-3h; the second stage sintering temperature is 500-800°C, and the sintering time is 1-3h.

10. Use of the catalyst prepared according to the preparation method according to any one of claims 1 to 9 in the preparation of monomethylamine.

Citation Information

Cited By

  • Spraying type catalyst for high-selectivity synthesis of monomethylamine and preparation method of spraying type catalyst

    CN122273568A